Assessment of decorative nano-plaster for fire safety - Olga G. Mukhamedzhanova; Angelina A. Alferova (Нанотехнологии в строительстве, 2025)
Introduction. In tests for fire and explosion hazard of materials, various factors influence the desired value and its variation. All these factors affect the correct classification of a material into a fire hazard group, which ultimately determines its potential use. For instance, on escape routes from a building, it is essential to use non-combustible materials (Group NС) for finishes. For example, on escape routes from the building, it is necessary to use non-combustible materials (group NС) for finishing. Therefore, to determine the actual group (class), it is necessary to determine not only the desired value, but also its data spread. Methods and materials. Baumit Nanopore decorative plaster was tested for flammability parameters to classify the material as either flammable or non f lammable. Results. Discussion. Tests of decorative plaster Nanopor “Baumit” showed the following results: loss of mass of the sample is P = 7.0±0.3%; temperature increase in the furnace is 4,6±1,7 ºC; duration of stable flame combustion is 1.0± 0.1 s. In accordance with p. 5.2 of GOST 30244-94 this building material is referred to non-combustible materials, because the values of flammability parameters are within the permissible norm. Loss of mass of decorative plaster samples after fire exposure decreased by only 7%, due to the loss of moisture during heating of plaster samples. And the uncertainty on the mass loss of decorative plaster is about 4%. The temperature increase in the oven during the tests of plaster is about 5 ºC, while the norm is not more than 50 ºC. Relative expanded uncertainty on the temperature rise in the furnace is 36%. Duration of stable flame combustion of plaster is 1 s, while the norm is not more than 10 s. The spread of data on this indicator is 10%. Conclusion. The analysis of the obtained data showed that the expanded uncertainty on flammability parameters ranges from 4 to 40%, which significantly affects the deviation of the measurement result from the true value, as well as the correctness of assigning the group (class) of fire danger to the material.